BIAYA RIIL DALAM TA’WIḌ PADA PEMBIAYAAN DI BSI DALAM PANDANGAN FATWA DSN-MUI - Fitroh Saidatul Robiah; Syarif Hidayatullah (JURNAL ILMIAH NUSANTARA, 2026)
There are still several findings related to ta'wiḍ. Based on Nadia Ananda Elsanti's 2017 research at BNI Syariah in Semarang, it was found that the amount of compensation (ta'wiḍ) was determined from the beginning of the agreement. Since the ta'wiḍ provision was included in the contract, the practice does not align with DSN MUI Fatwa No. 43/DSN-MUI/VIII/2004. This study aims to examine the practice of real costs as ta'wiḍ in Sharia Home Ownership Financing for defaulting customers at BSI KCP Bekasi Kalimalang Plaza and to analyze its conformity with Fatwa No. 129/DSN-MUI/VII/2019. Using a qualitative case study with a normative-empirical legal approach, data were collected through interviews, observations, and literature review. The study found that real costs are not predetermined in the contract but are determined through deliberation and restructuring, and this practice aligns with the fatwa, applying only if default actually occurs.